Pelatihan Master of Ceremony (MC) Acara Resmi Bagi Guru di SD IT Ar Royan Kota Padang - Bahardur, Iswadi; Afrinda, Putri Dian (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2023)
In the context of communication needs in public spaces, the role of a Master of Ceremony (MC) is currently considered very important, not only for informal events, but also for very formal events. It is said that because in official events, the MC is the spearhead who delivers or guides the event, from the opening to the closing of the event. Based on this idea, Master of Ceremony (MC) training for important official events is given to all parties who have an interest in this, including teachers at SD IT Ar Royan Padang. The official MC training activity was given to six teachers at SD IT Ar Royan through lecture methods and practical methods or performance for two days. After completing the training, it was clear that there were three main problems faced by the six training participants, namely a) their ability to manage their vocals was not optimal; b) body language that is not in accordance with the performance needs of an MC at an official event; and c) inadequate mastery of Indonesian grammar. The implication of the results of this activity is that it is important for SD IT Ar Royan to hold similar training activities with more varied methods and approaches.